Simulação da destilação molecular de filme descendente para o petróleo - Lopes, Herbert Senzano (2014)
The heavy part of the oil can be used for numerous purposes, e.g. to obtain lubricating oils. In this context, many researchers have been studying alternatives such separation of crude oil components, among which may be mentioned molecular distillation. Molecular distillation is a forced evaporation technique different from other conventional processes in the literature. This process can be classified as a special distillation case under high vacuum with pressures that reach extremely low ranges of the order of 0.1 Pascal. The evaporation and condensation surfaces must have a distance from each other of the magnitude order of mean free path of the evaporated molecules, that is, molecules evaporated easily reach the condenser, because they find a route without obstacles, what is desirable. Thus, the main contribution of this work is the simulation of the falling-film molecular distillation for crude oil mixtures. The crude oil was characterized using UniSim® Design and R430 Aspen HYSYS® V8.5. The results of this characterization were performed in spreadsheets of Microsoft® Excel®, calculations of the physicochemical properties of the waste of an oil sample, i.e., thermodynamic and transport. Based on this estimated properties and boundary conditions suggested by the literature, equations of temperature and concentration profiles were resolved through the implicit finite difference method using the programming language Visual Basic® (VBA) for Excel®. The result of the temperature profile showed consistent with the reproduced by literature, having in their initial values a slight distortion as a result of the nature of the studied oil is lighter than the literature, since the results of the concentration profiles were effective allowing realize that the concentration of the more volatile decreases and of the less volatile increases due to the length of the evaporator. According to the transport phenomena present in the process, the velocity profile tends to increase to a peak and then decreases, and the film thickness decreases, both as a function of the evaporator length. It is concluded that the simulation code in Visual Basic® language (VBA) is a final product of the work that allows application to molecular distillation of petroleum and other similar mixtures.